Emeviler ve Abbasîler dönemindeİstanbul kuşatmaları - Adıgüzel, Mehmet (My University, 2010)
İstanbul, siyasî, iktisadî ve kültürel inkişaflara müsait olan coğrafî mevkiinden dolayı tarihin akışı içinde her dönem, ulaşılmak istenen bir cazibe merkezi olmuştur. Nitekim Müslümanlar da Hz. Peygamber'in teşvikiyle erken dönemden itibaren bu şehre hâkim olmayı hedeflemişler ve bu amaçla kuşatmalarda bulunmuşlardır. Bu bağlamda, araştırmada Emeviler ve Abbasîler dönemindeki İstanbul kuşatınalan ve bu kuşatmalara katılan meşhur şahsiyetler ele alınmış, erken dönem İslam-Bizans mücadelesine genel hatlarıyla değinilmiştir.

istanbul, the politikal, ekonomic and cultural developmetts locality the availability of each term in the indirect flow of history, reached a center of attraction has been requested. Indeed, the speed of the Prophet Islam encouragement from the early period and this reason. A siege of this city targeted judges were found the execute. In this context, the research study, the Umayyads and the Abbasids during the siege of Istanbul and discussed this sieges been taken, members organizations participating on the early Byzantine struggle term in Islam in general terms are mentioned.
Keywords: Abbasîler; Emeviler; Ortaçağ